2021
DOI: 10.30919/esmm5f1146
|View full text |Cite
|
Sign up to set email alerts
|

Achieving High Value Utilization of Bio-oil from Lignin Targeting for Advanced Lubrication

Abstract: High-value utilization of biomass has been driven by increasingly growing industrial demands. Herein, we offer a strategy composed of depolymerization and esterification reaction of lignin to transfer to bio-oil with high liquid yield (79.75~85.25%), which is demonstrated as a high performance lubricant. Overall, the bio-oil has the excellent lubrication properties, where a significant wear reduction of 97.6% was observed as compared with polyethylene glycol 200. Meanwhile, the more ether and less acid in bio-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 51 publications
(56 reference statements)
0
14
0
Order By: Relevance
“…As is well known, biomaterials have attracted increasing attention during the past few decades due to their crucial role in the food industry, 1 wastewater treatment, 2 energy storage devices, 3,4 tissue engineering, 5,6 and regenerative medicine 7–9 . Today, there is a growing interest in recovering biomass residues to produce efficient biomaterials such as lignin, 3,10 cellulose, 11 and protein 12 . Because of environmental protection goals, much research has been done on developing sustainable biofuels from lignin 10 or employing cellulose‐based materials as a flexible electrode component in wearable sensing or medical devices 4,9,11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As is well known, biomaterials have attracted increasing attention during the past few decades due to their crucial role in the food industry, 1 wastewater treatment, 2 energy storage devices, 3,4 tissue engineering, 5,6 and regenerative medicine 7–9 . Today, there is a growing interest in recovering biomass residues to produce efficient biomaterials such as lignin, 3,10 cellulose, 11 and protein 12 . Because of environmental protection goals, much research has been done on developing sustainable biofuels from lignin 10 or employing cellulose‐based materials as a flexible electrode component in wearable sensing or medical devices 4,9,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Today, there is a growing interest in recovering biomass residues to produce efficient biomaterials such as lignin, 3,10 cellulose, 11 and protein 12 . Because of environmental protection goals, much research has been done on developing sustainable biofuels from lignin 10 or employing cellulose‐based materials as a flexible electrode component in wearable sensing or medical devices 4,9,11 . It is a known fact that numerous native human tissues such as muscles, tendons, ligaments, and skin are soft and elastic.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have explored in many ways to change the characteristics of the lubricant oils. [10][11][12][13][14][15] In particular, oxides are more and more used as lubricating oil additives because of their advantages in hardness, stability and morphology. [16][17][18] It is reported that boron oxide (B 2 O 3 ) and alumina (Al 2 O 3 ) nanoparticle additives can improve lubrication properties of lubricant oil prominently.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that there will be 12 billion tons of plastic waste in the world by 2050. Thus, there is an urgent need to identify solutions for recycling and/or reusing this material. At present, poly­(ethylene terephthalate) (PET) is the most common plastic-bottle waste. PET is incredibly tough and lightweight, while also exhibiting high tensile impact strength, abrasion resistance, and processing performance. , PET is recyclable but with a slight decrease in its mechanical properties after each cycle.…”
Section: Introductionmentioning
confidence: 99%